2021
DOI: 10.4103/jhrs.jhrs_90_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the vegan diet on sperm quality and sperm oxidative stress values: A preliminary study

Abstract: Background: Insufficient nutrition and inappropriate diet have been related to many diseases. Although the literature confirms the hypothesis that particular nutritional factors can influence the quality of semen, until today, there are no specific dietary recommendations created for infertile males. Since the male contribution to the fertility of a couple is crucial, it is of high importance to determine the dietary factors that can affect male fertility. Aim: The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Overall, 73 articles were selected for full-text screening. Finally, 20 eligible articles 14,28,31,33,34,[37][38][39][43][44][45][46][47][48][49][50][51][52][53][54] were included for qualitative synthesis, of which 16 were appropriate for quantitative synthesis. 28,31,33,34,[37][38][39]44,45,[47][48][49][51][52][53][54] The detailed selection process is shown in Figure 1.…”
Section: Study Selection Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 73 articles were selected for full-text screening. Finally, 20 eligible articles 14,28,31,33,34,[37][38][39][43][44][45][46][47][48][49][50][51][52][53][54] were included for qualitative synthesis, of which 16 were appropriate for quantitative synthesis. 28,31,33,34,[37][38][39]44,45,[47][48][49][51][52][53][54] The detailed selection process is shown in Figure 1.…”
Section: Study Selection Processmentioning
confidence: 99%
“…Studies were published between 1982 and 2021 and were conducted mainly in the United States (n = 8), 28,39,[47][48][49][51][52][53] followed by the United Kingdom (n = 5) 33,34,43,44,54 and Canada (n = 2). 14,37 Also, one study was reported from each one of the following countries (Chile, 46 Italy, 45 India, 50 Belgium 38 and Germany 31 ). Eighteen studies were designed as crosssectional and two studies as case-control.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations